Integration of GIS and AI in Urban Planning and Disaster Management - Paritosh Upreti; Pratap Bisht; Gauri (International Journal of Satellite Remote Sensing, 2025)
The rapid pace of urbanization, combined with the increasing frequency and intensity of natural disasters, necessitates the development of innovative solutions for urban planning and disaster management. Geographic information systems (GIS) and artificial intelligence (AI) have emerged as transformative technologies capable of addressing these challenges. GIS provides a robust framework for spatial data analysis, while AI enhances decision-making through predictive analytics and automation. This paper explores the integration of GIS and AI to foster smart urban planning and improve disaster management strategies. It highlights their combined application in urban growth management, infrastructure optimization, sustainability monitoring, disaster prediction, and response. Through a review of current case studies and real-world applications, this paper illustrates how these technologies can enhance the resilience and sustainability of urban environments. Despite the promising potential, the paper also addresses the challenges associated with data integration, technological barriers, and ethical concerns. Finally, it outlines future trends and opportunities for further integration of GIS and AI in creating smarter, more disaster-resilient cities.
Keywords: Artificial Intelligence (AI); Environment; disaster management; geographic information system (GIS); urban planning